The Impact of Teachers’ Personality Competence and Students’ Attitudes on the Quality of Learning - Ach. Baidowi; Wan Khairul Aiman Wan Mokhtar; Muhammad Haris; Mohd Ziaolhaq Qazi Zada; Mega Suteki (Journal Emerging Technologies in Education, 2024)
Background. The quality of education in Indonesia is still stagnant, as evidenced by students’ achievements, which have not shown significant changes. This is influenced by the competence of teachers, who are not yet fully professional. Purpose. This research aims to reveal the impact of teachers’ personality competence and students’ attitudes on the quality of learning, both partially and simultaneously. Method. This study employs a quantitative method with a correlational approach, involving 57 students from SDN Pangilen 3 Sampang in grades 4, 5, and 6. The sampling technique used is saturated sampling. Data was collected through a questionnaire with a Likert scale ranging from strongly agree (5) to strongly disagree (1). Data processing includes descriptive statistical analysis, prerequisite tests such as normality and linearity, as well as validity and reliability testing. Hypothesis testing is conducted through multiple regression analysis, including simultaneous testing (F test) and partial testing (t test) to analyze the contributions between variables. Results. It shows that teachers’ personality competence and students’ attitudes have a significant impact on the quality of learning, with Sig. values of 0.000 and 0.004, respectively. The simultaneous test confirms the collective influence of both variables, with teachers’ competence contributing 34.1% and students’ attitudes contributing 19.5%. The dominance of teachers’ competence in affecting the quality of learning is evident from its relative contribution of 63.6%. Conclusion. This research emphasizes the importance of enhancing teachers’ personality competence to improve the quality of learning in schools.